2019 IEEE Conference on Virtual Reality and 3D User Interfaces (VR) 2019
DOI: 10.1109/vr.2019.8797921
|View full text |Cite
|
Sign up to set email alerts
|

TacTiles: Dual-Mode Low-Power Electromagnetic Actuators for Rendering Continuous Contact and Spatial Haptic Patterns in VR

Abstract: Figure 1: TacTiles are small and light form factor tactile elements that can be placed anywhere on the hand to render contact with virtual objects and enable haptic surface exploration. An individual TacTile is able to produce 200 mN of holding force on the finger without any power draw and is dampened on one side to minimize release vibrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…Several works focused on the transition between making and breaking contact [17], [18], [19], [20], [21]. For example, Vechec et al [19] opted for a wearable haptic device made of several actuators which can be controlled to engage or disengage a pin against the user's skin, at high rate, using electromagnetic actuators. For example, Kuchenbecker et al [20] endowed a grounded haptic device with a passive cutaneous end-effector.…”
Section: Related Workmentioning
confidence: 99%
“…Several works focused on the transition between making and breaking contact [17], [18], [19], [20], [21]. For example, Vechec et al [19] opted for a wearable haptic device made of several actuators which can be controlled to engage or disengage a pin against the user's skin, at high rate, using electromagnetic actuators. For example, Kuchenbecker et al [20] endowed a grounded haptic device with a passive cutaneous end-effector.…”
Section: Related Workmentioning
confidence: 99%
“…For example, one participant reported that they perceived the slower patterns as smooth circles, while the faster ones seemed more "random". The exhibited JND allows for several levels of speed rendering, and its possible that other patterns may exhibit different levels of sensitivity [10].…”
Section: Jnd Of Speedmentioning
confidence: 99%
“…Pin array haptic interfaces offer a way to increase the fidelity and localization of haptic feedback on the user's hand. They come in the form of touchable surfaces [5]- [8], wearables [9], [10], and embedded in handheld platforms [11]- [14]. It is desirable to provide varying levels of force intensity as it allows for a larger dynamic range when rendering tactile stimuli.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the concept of wearable devices has been proposed, and tactile feedback has been implemented in wearable devices to transfer information through a new medium, i.e., the skin. So far, various wearable tactile devices have been proposed using piezoelectric actuators, cylindrical motors, servo motors, electromagnetic actuators, pneumatic or hydraulic actuators, and shape memory alloy actuators [6][7][8][9][10][11][12][13][14]. Nonetheless, to create a light-weight, flexible, and high output force tactile device especially for use in a wearable interfaces, more research needs to be done on other soft actuators.…”
Section: Introductionmentioning
confidence: 99%